Discussion of “computational electrocardiography: revisiting holter ECG monitoring” - Baumgartner, Christian; Caiani, Enrico G.; Dickhaus, Hartmut; Kulikowski, Casimir A.; Schiecke, Karin; Bemmel, Jan H. van; Witte, Herbert (Methods of information in medicine, 2016)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the paper “Computational Electrocardiography: Revisiting Holter ECG Monitoring” written by Thomas M. Deserno and Nikolaus Marx. It is introduced by an editorial. This article contains the combined commentaries invited to independently comment on the paper of Deserno and Marx. In subsequent issues the discussion can continue through letters to the editor.
Gesehen am 04.05.2020